Psychological impact of an adult ADHD diagnosis - Young, Zoe (2017)
The study aimed to explore the processes people go through when diagnosed with ADHD in adulthood from a psychological perspective. ADHD has recently been recognised as affecting adults. Limitations exist in the breadth and depth of qualitative research into the experiences of those receiving an ADHD diagnosis in adulthood. Existing research is largely descriptive, with a prominent focus on pharmacological treatment. As such, psychological processes have not been sufficiently explored. Without ADHD-specific models of adjustment, the literature on identity, cognitive adaptation and stigma is examined.